Turkish dilemma after Operation Desert Storm (1990-1991): an analysis of negative consequences - Canci, Haldun; Sen, Sevket Serkan (Routledge Journals, Taylor & Francis Ltd, 2010)
This article analyzes the internal criticism of the political and economic consequences of Turkish support for the UN international coalition against Iraq's occupation of Kuwait in 1990. Was this criticism warranted and justifiable or not? To answer the research question, certain issues like the Kurdish problem, relations with other countries in the region, and economic issues will be examined in light of Operation Provide Comfort I and II regimes and the criticism they caused within Turkish politics. The paper will also examine the debate on the establishment of no-fly zones over northern Iraq, as well as the debate on the rise in violence.
Keywords: Operation Desert Storm; Operation Provide Comfort; Turkish foreign policy; Turkish politics; Kurdish problem; northern Iraq